Glass Technology in Natural Light Glasses on Aperture Element in The Architecture World - Muhammad Rijal; Pedia Aldy (International Conference on Engineering and Technology Development (ICETD), 2013)
The glass is formed by element which during the time without you realize possible there are at your house backyard or your environment work. Glass material spread over above island in earth. This matter become in the world of architecture nusantara if we do not exploring existence of glass. In the west technological till in this time continue explored how in a moment wait glass to substitution element of especial structure ( which during the time only exploiting concrete and steel in the world of construction). This article only small explanation about glass from some important note pursuant to source of reference representing, in meaning glass material from the aspect of look into light natural at aperture element in the world of architecture. In this article, writer try to present synchronized simple explanation but about history attendance of glass started only as decorator till the part of construction. Writer present very famous aperture element buttonhole in architecture world, colaboration with glass material by presenting some environmental effect and into illumination systems innovation to load light natural maximally which framed in glass till attend again explore in architecture worl